Geotechnical Aspects of Explosive Compaction - Mahdi Shakeran; Abolfazl Eslami; Majid Ahmadpour (Shock and Vibration)
Explosive Compaction (EC) is the ground modification technique whereby the energy released from setting off explosives in subsoil inducing artificial earthquake effects, which compact the soil layers. The efficiency of EC predominantly depends on the soil profile, grain size distribution, initial status, and the intensity of energy applied to the soil. In this paper, in order to investigate the geotechnical aspects, which play an important role in performance of EC, a database has been compiled from thirteen-field tests or construction sites around the world, where EC has been successfully applied for modifying soil. This research focuses on evaluation of grain size distribution and initial stability status of deposits besides changes of soil penetration resistance due to EC. Results indicated suitable EC performance for unstable and liquefiable deposits having particle sizes ranging from gravel to silty sand with less than 40% silt content and less than 10% clay content. However, EC is most effective in fine-to-medium sands with a fine content less than 5% and hydraulically deposited with initial relative density ranging from 30% to 60%. Moreover, it has been observed that EC can be an effective method to improve the density, stability, and resistance of the target soils.